Telephone hotline for aging: Information needs, quality of service, and insights. (September 2018) - Cohen-Mansfield, Jiska; Perach, Rotem; Kadmon Stern, Tali; Albeck, Shulamith; Rotem, Dror; Arnow, Tamara Lynn; Lerman, Yaffa
This study examined the reasons for use and the utility of an aging-focused telephone hotline. The most common topic of inquiry was care, followed by referrals for institutional placement and financial queries. Advice from hotline professionals was reported to be useful and helpful. Yet the issue of the query was not resolved in half of the cases. Some queries may be addressed by enhancing hotline procedures, but others reflect general unmet needs that require wider systematic social changes in the information, system, and financial domains. Analysis of hotline calls can be useful for identifying areas, both for improvement for the hotline and for society.